EFL STUDENTS’ VOCABULARY MASTERY THROUGH VOCABULARY NOTEBOOK DURING ONLINE LEARNING - I Made Permadi Utama; Siti Syafi’atul Qomariyah (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2022)
Online learning is a teaching and learning activity using the internet network. This is the impact of the Covid 19 pandemic, which requires educators and students to carry out the teaching and learning process remotely with the aim of reducing the risk of spreading the virus from interactions in the classroom. In line with this situation, Vocabulary Notebook is a strategy that can be used by teachers in carrying out online teaching and learning activities, especially in mastering English vocabulary for EFL students. In order to see the effect of using Vocabulary Notebook on EFL students' English vocabulary, the researchers conducted this study with the aim to know the impact of Vocabulary Notebook on EFLs tudents' vocabulary mastery during online learning. In this study, researchers have applied an experimental research method with a posttest only control group design. The population in this study was 84 EFL students where the researcher divided the 84 students into two groups as the sample, group A was 27 students as the experimental group, and group B was 27 students as the control group. Thus, the number of samples in this study was 54 students. Based on the findings, the average score of the experimental group was higher than the control group, where the average score of the experimental group was 65,926 while the average score of the control group was 56,741. Furthermore, based on data analysis, it is found that the t-test score was 2.607 which is higher than the t-table (1.675). It can be concluded that Vocabulary Notebook has positive results on EFL students' vocabulary mastery during online learning.